Designing gender- and youth-responsive agronomic solutions - Lambrecht, Isabel B.; Ma, Ning; Ragasa, Catherine; Cole, S.; Kreye, C.; Peter, H.; Yergo, W.; Arouna, A.; Tijjani, K.; Shehu, B.M.; Ibrahim, A.; Kazuki, S.; et al. (CGIAR Initiative on Excellence in Agronomy, 2023)
This Report was produced as part of the CGIAR Excellence in Agronomy (EiA) Initiative’s effort to ensure that women and youth are well integrated into to the work of the Initiative’s Use Cases and that the EiA Initiative is achieving its gender- and youth-specific impacts: that women and men, youth and non-youth equally participate in and benefit from the agronomic solutions developed, validated, and piloted by Use Cases, and that social innovations that empower women and transform unequal power relations and restrictive social and gender norms are piloted and promoted. 4 Study Report: Sasakawa Africa Association Nigeria Use Case KEY FINDINGS: This report covers the study area of the Sasakawa Africa Association Nigeria (SAA Nigeria) Use Case in the Northwest (Kano and Kaduna) and North Central (Nasarawa), based on interviews conducted in June and July 2023. The study sites are in Northwest (Kano and Kaduna) and North Central (Nasarawa).